Nanoparticle‐Conjugate TLR7/8 Agonist Localized Immunotherapy Provokes Safe Antitumoral Responses. Issue 45 (1st October 2018) - Nuhn, Lutz; De Koker, Stefaan; Van Lint, Sandra; Zhong, Zifu; Catani, João Portela; Combes, Francis; Deswarte, Kim; Li, Yupeng; Lambrecht, Bart N.; Lienenklaus, Stefan; Sanders, Niek N.; David, Sunil A.; et al.
Abstract: Localized therapeutic modalities that subvert the tumor microenvironment from immune‐suppressive to pro‐immunogenic can elicit systemic antitumor immune responses that induce regression of directly treated as well as nontreated distal tumors. A key toward generating robust antitumor T cell responses is the activation of dendritic cells (DCs) in the tumor microenvironment. Treatment with agonists triggering various pattern recognition receptors is very efficient to activate DCs, yet suffers from the induction of serious immune‐related adverse effects, which is closely linked to their unfavorable PK/PD profile causing systemic immune activation and cytokine release. Here, it is reported that nanoparticle conjugation of a highly potent TLR7/8 agonist restricts immune activation to the tumor bed and its sentinel lymph nodes without hampering therapeutic antitumor efficacy. On a mechanistic level, it is confirmed that localized treatment with a nanoparticle‐conjugated TLR7/8 agonist leads to potent activation of DCs in the sentinel lymph nodes and promotes proliferation of tumor antigen‐specific CD8 T cells. Furthermore, therapeutic improvement upon combination with anti‐PDL1 checkpoint inhibition and Flt3L, a growth factor that expands and mobilizes DCs from the bone marrow, is demonstrated. The findings provide a rational base for localized tumor engineering by nanomedicine strategies that provide spatial control over immune‐activation. Abstract : Conjugation of TLR7/8 agonist provides spatial control of immune activation to avoid systemic inflammation. Local immune stimulation allows the generation of tumor‐specific immune responses that show therapeutic improvement in combination with checkpoint inhibitor treatment to combat immune suppression.